2017
DOI: 10.1002/jcb.26296
|View full text |Cite
|
Sign up to set email alerts
|

AAV delivery of GRP78/BiP promotes adaptation of human RPE cell to ER stress

Abstract: Adeno associated virus (AAV)-mediated gene delivery of GRP78 (78 kDa glucose-regulated protein) attenuates the condition of endoplasmic reticulum (ER) stress and prevents apoptotic loss of photoreceptors in Retinitis pigmentosa (RP) rats. In the current study we overexpressed Grp78 with the help of AAV-2 in primary human retinal pigmented epithelium (hRPE) cell cultures and examined its effect on cell response to ER stress. The purpose of this work was studying potential stimulating effect of GRP78 on adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
(184 reference statements)
0
14
0
Order By: Relevance
“…Multiple reports have proposed regulating the ISR to ameliorate retinal degeneration 5,3537 . In the present study, we provide evidence suggesting that regulation of eIF2α alone may not be sufficient to significantly change protein synthesis rates or impact retinal cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple reports have proposed regulating the ISR to ameliorate retinal degeneration 5,3537 . In the present study, we provide evidence suggesting that regulation of eIF2α alone may not be sufficient to significantly change protein synthesis rates or impact retinal cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have shown that subretinal delivery of AAV5-BiP to a transgenic rat model of RP (P23H) results in reduction of PR cell death and improved ERG amplitudes [115]. Furthermore, a study in primary human retinal pigmented epithelium cells (hRPE) showed that AAV2-BiP promotes the survival of these cells under ER stress [116]. Both studies suggest that these improvements are due to a suppression of apoptosis by downregulation of CHOP protein levels.…”
Section: Therapeutic Approaches To Restore Protein Balancementioning
confidence: 99%
“…Interestingly, the virally transformed HEK293T was most prominent in extracellular HSP90α. Prominent representation by GRP78 in extracellular HSP complexes is significant with regard to a multi-modal influence on tumorigenesis and as the hub of the translational ER stress response (Ghaderi et al 2018;Steiner et al 2017;Thomaidou et al 2018). Interestingly, the clearest differentiation of HSP content was seen for distribution of inducible HSP70-1/2; while abundant in HEK293T, PSMs were not detected in equivalent eHSP of U87.…”
Section: Proteomic Analysismentioning
confidence: 99%